Sharia Financial Literacy Index as a Preference in Interest of Saving at Islamic Banks - Arfatun Arfatun; Muh Tasrif; Lila Alwyah (IQTISHADUNA, 2023)
The research aims to describe the potential of the Islamic financial literacy index in increasing people's interest in saving at Islamic Banks in West Nusa Tenggara Province. The method used is descriptive quantitative with a systematic literature review approach. The research findings show that the Islamic financial literacy index has the potential to increase the Islamic financial inclusion index. Islamic financial literacy is specified into high knowledge found in Islamic Banks and Savings is the most recognized product. Those with high Islamic financial literacy are retirees, besides those people with a vulnerable age of 25 years and over and those who work as workers. Areas that have the potential to develop Islamic financial inclusion are Mataram City and North Lombok Regency. This research contributes to providing recommendations to Islamic Banks to be considered for developing Islamic business, as well as topics to be developed in the future.